2013
DOI: 10.1117/12.2030342
|View full text |Cite
|
Sign up to set email alerts
|

Round-robin measurements of toroidal window

Abstract: We have performed a round-robin study of surface irregularity measurements of a free-form toroidal window. The measurement tools were a Leitz scanning CMM at Optimax Systems, Inc., an UltraSurf, a non-contact measuring system at OptiPro Systems, a Zeiss scanning CMM at OptiPro Systems, a F25 micro-CMM at Carl Zeiss Industrial Metrology, and an ASI(Q) TM at QED Technologies. Each instrument resulted in a 2.5D surface error map. The measurements were compared with multiple analysis settings. The different analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There have been no formal comparisons of areal surface texture measurement, although some comparisons of optical instruments have shown predictable variations [130,150] as do comparisons of AFM and optical instruments [131].…”
Section: Comparisonsmentioning
confidence: 99%
“…There have been no formal comparisons of areal surface texture measurement, although some comparisons of optical instruments have shown predictable variations [130,150] as do comparisons of AFM and optical instruments [131].…”
Section: Comparisonsmentioning
confidence: 99%
“…The CMM has a touch trigger probe that scans surface and outputs the deviation of the measured surface from the nominal shape. We have participated in a round-robin study 6 of a freeform toroid window which showed that the CMM is accurate to about 1 µm peak-to-valley or 0.2 µm rms, Figure 4. To move beyond the precision provided by the CMM, we are using two methods.…”
Section: Measurementmentioning
confidence: 99%
“…Left: the CMM used for measuring freeform optics; middle: touch trigger probe used in the CMM measurements; right: the standard deviation of a set of round robin measurements of a toroid window6 indicating the accuracy of the CMM is near 0.2 µm.…”
mentioning
confidence: 99%
“…The area of freeform metrology is currently under investigation by a number of different research groups. [7][8][9][10] Achievable surface form error of freeform surfaces is a function of the complexity of the shape and the uncertainty of the measurement method. A typical scanning probe coordinate measuring machine is limited to approximately ±1 µm PV form error.…”
Section: Current Freeform Optical Manufacturing and Testing Processesmentioning
confidence: 99%
“…A typical scanning probe coordinate measuring machine is limited to approximately ±1 µm PV form error. [10] Surface smoothing may or may not be necessary based on the application and the severity of resulting midspatial frequency errors on the surface. Smoothing can be done implementing the VIBE smoothing process.…”
Section: Current Freeform Optical Manufacturing and Testing Processesmentioning
confidence: 99%